HUBUNGAN KEPEMIMPINAN KEPALA SEKOLAH DAN SIKAP PROFESIONALISME GURU DENGAN PRESTASI BELAJAR IPA SISWA KELAS IX SMP ADVENT TIMIKA - ROIDA SIREGAR; ALFRED ANTOH (Program Magister Pendidikan IPA, Program Pascasarjana Universitas Cenderawasih, 2018)
A research has been done to determine the relationship between the leadership of Pricipal and Teacher Professionalism Attitudes to Science achievement of IX Grader of Junior Adventist Academy. The method used in this study is the correlation method with a target of the population of the of Junior High School Adventist Timika. The population is a bout 150 students and the number of research samples is 32 students. The result shows that there is a significant relationship between the leadership of principal with the science learning achievement of Junior High School the IX graders and the effective contribution 76,7%, there is significant relationship between the teachers professionalism with the science learning achievement of Junior High School the IX graders and the effective contribution 76,7%, there is a significant relationship between the leadership of principal and the techers professionalism with the science learning achievement of Junior High School the IX graders and the effective contribution 76,7%. The results of this study are expected to be useful in improving the quality of school leadership and teacher professionalism, as principal leadership and teacher professionalism can significantly increase student achievement. Keywords : Principal Leadership, teacher professionalism, Attitude Achievement students.